Revenimento do aço inoxidável supermartensítico 15Cr: aspectos microestruturais e comportamento de corrosão eletroquímica - Souza, Celso Antônio Galbiati e Turazza de (Universidade Federal de São Carlos, 2023)
The supermartensitic steels are a new class of stainless steels in development and consolidation as commercial products for the oil and gas industry, marked by significant changes in the chemical composition of conventional martensitic stainless steels, such as the reduction of the C content to <0,03 %wt, combined with the addition of Ni and Mo. Recently, new alloys containing higher amounts of Cr have been developed, such as supermartensitic stainless steels 15Cr (or super 15Cr), in order to offer na interesting combination of high mechanical strength, toughness, weldability and corrosion resistence in aggressive environments (high concentrations of chlorides, carbon dioxide, hydrogen sulfide etc.). However, these steels are still little used in the construction of components and equipment in Petrobras operating units, because many of their properties are still reasons for investigation, such as the tempering heat treatment effect on corrosion resistence. In this way, the objectives of this dissertation was characterize the microstructure and evaluate the electrochemical corrosion behavior of a super 15Cr in function of the tempering heat treatment. Futhermore, the characterization of the samples was carried out through optical microscopy (OM), scanning eléctron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and measurement of Vickers hardness. Finally, the anodic behavior of this material in a diluted solution of sulfuric acid (H2SO4) was evaluated by potentiodynamic polarization measurements, the degree of depletion in Cr was determined through the technique of double loop electrochemical potentiokinect reactivation (DL-EPR) and the pitting corrosion behavior was observed by anodic polarization tests in 3,5 % NaCl solution. The results showed that the tempering heat treatments promote the appearance of reverse austenite, which increases the degree of Cr depletion of the material. In addition, there was a tendency for Epitting to decrease with increasing temperature and, despite the increase in the degree of Cr depletion, there was no significant variation in Epitting.
Tempering of 15Cr supermartensitic stainless steel: microstructural aspects and electrochemical corrosion behavior
Keywords: Aço inoxidável; Supermartensítico; Super 15Cr; Revenimento; Austenita reversa; Polarização; Corrosão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA